(untitled) (Global Journal of Science Frontier Research, 2015)
In most African Countries, increase in Gross Domestic Products (GDP) has not translated to economic growth and development. For some decades had a lot of contestson economic growth and development has been a serious issues.The focus of this study is to analysing the effects of economic determinants on economic growth rate in some African Countries by employing panel data analysis. Yearly data were used from 1990 to 2013 time period. The data was obtained from the world economic outlook database of the International Monetary Fund (IMF), for probing the effects of these variables on growth rate in some selected African countries which include: Nigeria, Algeria, Angola, Benin, Botswana, Burundi, Cape-Verde, Cameroun, Central African Republic, Chad, Republic Of Congo, Cote di’ Voire, Egypt, Equatorial-Guinea, Ethiopia, Gabon, Ghana, Guinea Bissau, Kenya, Lesotho, Madagascar, Mali, Mauritius, Morocco, Mozambique, Niger, Rwanda, Senegal, Seychelles, Sierra Leone, South Africa, Sudan, Swaziland, Tanzania, Togo, Tunisia, and Uganda. The effects of 6 macroeconomic variables on GDP were critically examined.